Existential concerns, community integration and psychological depression among female stroke survivors in Nigeria - Olaleye, Olubukola A.; Olajide, Ayomide T. (Frontiers in Stroke, 2025)
IntroductionFemale stroke survivors experience considerable vulnerabilities and existential concerns, shaped by sociocultural factors and gender roles, which heighten stroke morbidity and limit community reintegration. Yet, the existential concerns of female stroke survivors in Nigeria, and their relationships with psychological depression and community reintegration have not been explored.MethodsA mixed-methods study was conducted among female stroke survivors recruited from selected hospitals in South-west, Nigeria. Community integration questionnaire, Existential concerns questionnaire, and the depression subscale of the Hospital anxiety and depression scale were used to assess community reintegration, existential concerns, and psychological depression, respectively. Six purposively selected female stroke survivors participated in a focus group discussion (FGD). Quantitative data were analyzed using Chi-square test at p < 0.05, while qualitative data were thematically analyzed.ResultsSeventy-five female stroke survivors aged 64.07 ± 14.03 years participated in the survey. The mean community reintegration, existential concerns and psychological depression scores were 12.24 ± 2.95, 9.77 ± 5.52, and 13.84 ± 4.71, respectively. The majority (n = 61; 81.3%) of the participants had a low level of community integration. Forty-seven (62.7%) reported a moderate level of existential concerns, while 32(42.7%) had psychological depression. There was a significant association between community reintegration and psychological depression (p = 0.02), and between existential concerns and psychological depression (p < 0.01). However, there was no association between community reintegration and existential concerns (p = 0.08). The five emergent themes from the FGD were: perception of stroke as a devastating condition; role disruption and loss of autonomy in the home, isolation and stigmatization in society, inadequate spousal support and sexual intimacy, work-related and financial concerns.ConclusionExistential concerns among participants were mostly related to social and family roles and were associated with poor emotional and mental wellbeing. Addressing these concerns through integrated care, delivered by a coordinated multidisciplinary team, could enhance emotional and mental wellbeing, and promote community reintegration among female stroke survivors.